2018
DOI: 10.1101/331108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zika virus infection at mid-gestation results in fetal cerebral cortical injury and fetal death in the olive baboon

Abstract: Zika virus (ZIKV) infection during pregnancy in humans is associated with an increased incidence of congenital anomalies including microcephaly as well as fetal death and miscarriage and collectively has been referred to a Congenital Zika Syndrome (CZS).Animal models for ZIKV infection in pregnancy have been developed including mice and macaques. While microcephaly has been achieved in mice via direct injection of ZIKV into the fetal brain or via interference with interferon signaling, in macaques the primary … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Non‐human primate studies have also provided support for myelin involvement in the pathogenesis of ZIKV infection of the CNS. Oligodendroglial development was impaired in fetuses of mid‐gestation olive baboons infected systemically with a French Polynesian ZIKV isolate (H/PF/2013; Gurung et al, 2019) and white matter hypoplasia were reported in preterm pigtail macaque following systemic infection of the pregnant dam with a Cambodian isolate (FSS13025; Adams Waldorf et al, 2016). As in the current study, these non‐human primates were killed before the long‐term consequences were known and it will be important for future studies to address later outcomes, within the limitations of animal welfare issues.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐human primate studies have also provided support for myelin involvement in the pathogenesis of ZIKV infection of the CNS. Oligodendroglial development was impaired in fetuses of mid‐gestation olive baboons infected systemically with a French Polynesian ZIKV isolate (H/PF/2013; Gurung et al, 2019) and white matter hypoplasia were reported in preterm pigtail macaque following systemic infection of the pregnant dam with a Cambodian isolate (FSS13025; Adams Waldorf et al, 2016). As in the current study, these non‐human primates were killed before the long‐term consequences were known and it will be important for future studies to address later outcomes, within the limitations of animal welfare issues.…”
Section: Discussionmentioning
confidence: 99%